Role of inflammatory aging in the development of age-related macular degeneration - A.S. Khalatyan; Yu. Yusef (РМЖ "Клиническая офтальмология")
A.S. Khalatyan, Yu. Yusef M.M. Krasnov Research Institute of Eye Diseases, Moscow, Russian Federation Aging is often accompanied by systemic inflammation known as ‘inflamm-aging'. This process is characterized by an increase in proinflammatory cytokines and a decrease in anti-inflammatory cytokines. Inflammatory aging is caused by both chronic subclinical inflammation from exogenous factors and intrinsic inflammatory processes associated with progressive mitochondrial degeneration. Age-related macular degeneration (AMD) is the primary cause of blindness and visual impairment in patients over 60 years of age in developed countries. The disease has a complex pathogenesis, with inflammation playing a central role in the degenerative processes in both dry and wet AMD. The development of AMD involves various pro-inflammatory stimuli, cells, mediators, and metabolic pathways. The pathogenesis of AMD begins with the thickening of Bruch's membrane caused by the accumulation of lipids and proteins, resulting in the formation of subretinal deposits called drusen. These deposits impede fluid outflow from retinal pigment epithelium (RPE) cells through Bruch's membrane, leading to an increased metabolic burden on the RPE. This cellular stress triggers a pro-inflammatory cascade. The purpose of this paper is to examine the current understanding of the role of inflammation in AMD and to explore potential new therapeutic approaches. Keywords: aging, inflammation, age-related macular degeneration, inflammatory aging, antiangiogenic therapy. For citation: Khalatyan A.S., Yusef Yu. Role of inflammatory aging in the development of age-related macular degeneration. Russian Journal of Clinical Ophthalmology. 2024;24(3):127–132 (in Russ.). DOI: 10.32364/2311-7729-2024-24-3-5.